PENGARUH TERAPI MUROTTAL AYATUL SYIFA’ TERHADAP WAKTU PULIH SADAR PASIEN PASCA GENERAL ANESTESI DI RS PKU MUHAMMADIYAHGAMPING - Eka Putri Arthaningsih Febrienka; Harmilah Harmilah; Sutejo Sutejo (Caring : Jurnal Keperawatan, 2018)
General anaesthesia makes the patient temporally unconscious. Anaesthesia techniques and doses of the medications administered may affect the patient's recovery consciousness period. Post-anaesthetic management is so important to prevent the complications of delayed recovery consciousness period such as airway obstruction, hypoxemia, hypercarbia, and aspiration. Murottal therapy is one of the non-pharmacological therapies that can provide hemodynamic stability, relaxing effect, peace of mind, and increased threshold of consciousness. The aim of this study was to know the effect of murottalayatulsyifa’ therapy in patient's recovery consciousness period in post-general anaesthetic at PKU Muhammadiyah Gamping Hospital. This research used quasi experiment method with post-only design. The research held in March-April 2018. The samples were 21 respondents of the treatment group (given murottal) and 21 respondents of the control group of post-general anaesthetic patients with purposive sampling technique. The result of this study showed that there was influence of murottal ayatul syifa’ therapy in patient's recovery consciousness period in post-general anaesthetic with (p-value) 0.000 (p <0.05). The average of the patient's recovery consciousness period in the treatment group was 5.14 minutes and the average of the patient's recovery consciousness period in the control group was 10.9 minutes. The conclusion of this study is there is effect of murottal ayatul syifa’ therapy in patient's recovery consciousness period in post-general anaesthetic.